The Generalized Twist for the Torsion of Piezoelectric Cylinders. (15th June 2017) - Ecsedi, István; Baksa, Attila
Abstract : In the classical theory of elasticity, Truesdell proposed the following problem: for an isotropic linearly elastic cylinder subject to end tractions equipollent to a torque T, define a functional τ ( u ) on Q such that T = K τ ( u ), for each u ∈ Q, where Q is the set of all displacement fields that correspond to the solutions of the torsion problem and K depends only on the cross-section and the elastic properties of the considered cylinder. This problem has been solved by Day. In the present paper Truesdell's problem is extended to the case of piezoelastic, monoclinic, and nonhomogeneous right cylinders.